Effect of imidapril on heterogeneity of slow component of delayed rectifying K+ current in rabbit left ventricular hypertrophic myocytes - Li, Yang; Lu, Zai-Ying; Xiao, Jian-Men; Ma, Jie; Niu, Hui-Yan; Liu, Nian; Ruan, Yan-Fei (Acta pharmacologica Sinica, 2003)
To investigate the transmural heterogeneous change of slow component of delayed rectifying potassium current in rabbit left ventricular hypertrophic myocytes and the effect of long-term treatment with imidapril (Imi). Rabbits were divided into hypertrophy group (left ventricular hypertrophy induced by partial ligation of abdominal aorta), Imi-treated group (surgical treatment as hypertrophy group was treated with Imi), and Sham-operated group as control. Whole-cell patch-clamp technique was used to record potassium currents. (1) Membrane capacitance was larger in hypertrophic cells than in sham-operated and Imi-treated cells. Action potential durations (APD) of epicardium (Epi), midmyocardium (M), and endocardium (Endo) were remarkably longer in hypertrophic cells than those in Imi-treated and sham-operated cells. The prolongation of APD90 of M was the most pronounced in three layer myocytes of hypertrophic group. (2) The densities of I(Ks,tail) of hypertrophic cells were reduced by Epi 25.3 %+/-2.9 %, M 38.0 %+/-3.7 % and Endo 20.3 %+/-4.7 % compared with those of sham-operated cells. The decrease of IKs,tail density was more pronounced in M than in Epi and Endo (n = 13, P<0.01 vs Epi or Endo). (3) The density of I(Kr,tail) in Imi-treated cells was not different from that in sham-operated cells significantly (n=10). Imi reduced prolongation of APD and inhibited the heterogeneous change of I(Ks,tail) in rabbit left ventricular hypertrophic myocytes.